The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/su14042098
|View full text |Cite
|
Sign up to set email alerts
|

Using Real Options Thinking to Value Investment Flexibility in Carbon Capture and Utilization Projects: A Review

Abstract: Carbon capture and utilization (CCU) is one of the key technologies that may help to reduce industrial emissions. However, the deployment of CCU is hampered by various barriers, including high levels of technical, policy and market uncertainty. The real options theory (ROT) provides a method to account for these uncertainties and introduce flexibility in the investment decision by allowing decisions to be changed in response to the evolution of uncertainties. ROT is already being applied frequently in the eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 54 publications
(216 reference statements)
0
2
0
Order By: Relevance
“…In the conclusion, LONGI's share price trend is good. Meanwhile, to reflect the unit risk-adjusted fund yield, it is necessary to calculate the Sharpe ratio using the Sharpe model [9][10], when the Sharpe ratio is positive, it can indicate that the average net value growth rate of the fund exceeds the risk-free rate during the measurement period, namely the investment fund is better than the bank deposit at this time. Finally, the Sharpe ratio of all three stocks is slightly greater than 0, which shows that it has investment value.…”
Section: Investment Analysismentioning
confidence: 99%
“…In the conclusion, LONGI's share price trend is good. Meanwhile, to reflect the unit risk-adjusted fund yield, it is necessary to calculate the Sharpe ratio using the Sharpe model [9][10], when the Sharpe ratio is positive, it can indicate that the average net value growth rate of the fund exceeds the risk-free rate during the measurement period, namely the investment fund is better than the bank deposit at this time. Finally, the Sharpe ratio of all three stocks is slightly greater than 0, which shows that it has investment value.…”
Section: Investment Analysismentioning
confidence: 99%
“…The uncertainties and risks of the real-world setting are typically neglected in this type of assessment. To include those uncertainties and risks, there is a growing stream of literature that analyzes investment decisions in CCS or CCU technologies in a dynamic framework, taking managerial flexibility into account (see Agaton (2021) and Lamberts-Van Assche and Compernolle (2022b) for an extensive review of real options applications in CCS and CCU respectively). Real options analysis presents a method to value flexibility in investment decisions, acknowledging the fact that decision-makers can delay investment decisions in practice (Dixit and Pindyck, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The uncertainties and risks of the real-world setting are typically neglected in this type of assessment. To include those uncertainties and risks, there is a growing stream of literature that analyzes investment decisions in CCS or CCU technologies in a dynamic framework, taking managerial flexibility into account (see Agaton (2021) and Lamberts-Van Assche and Compernolle (2022b) for an extensive review of real options applications in CCS and CCU respectively).…”
Section: Introductionmentioning
confidence: 99%
“…Real options analysis presents a method to value flexibility in investment decisions, acknowledging the fact that decision-makers can delay investment decisions in practice (Dixit and Pindyck, 1994). A literature review on real options analysis for CCU projects revealed that the CO 2 price is the most commonly included source of uncertainty in investment decisions for CCU projects (Lamberts-Van Assche and Compernolle, 2022b). The CO 2 price in the EU ETS can also be affected by policymakers, by changing the emissions cap and the number of emissions allowances issued.…”
Section: Introductionmentioning
confidence: 99%